Changes in patient activation in people starting dialysis: A prospective longitudinal, observational study. Issue 3 (19th April 2022) - Hussein, Wael F.; Bennett, Paul N.; Carrasco, Anna; Sun, Sumi; Reiterman, Marc; Watson, Emily; Schiller, Brigitte
Abstract: Introduction: Increased patient activation is associated with improved health outcomes; however, little is known about patient activation in people with end‐stage kidney disease at the start of their dialysis journey. This study aimed to measure activation status changes over the first 4 months of dialysis. Methods: Prospective, longitudinal, and observational study. Incident patients initiating dialysis at 25 in‐center hemodialysis and 17 home dialysis programs across three US states managed by the same dialysis provider completed the 13‐item Patient Activation Measure (PAM‐13) survey at baseline (month 1 after commencement of dialysis) and follow‐up (month 4). The survey yields a score (0–100) that corresponds to four levels (1–4), with higher scores or levels indicating higher activation. Findings: One hundred eighty‐two participants (139 center, 43 home) completed both baseline and follow‐up surveys. Mean age was 60 ± 15 years, 40% female. Mean PAM‐13 scores were 65.1 ± 16.8 and 64.8 ± 17.8 at baseline and follow‐up, respectively; mean intraindividual change: −0.3 ± 17.3. The proportions of patients at levels 1–4 at baseline were 11%, 23%, 35%, and 31% respectively. At follow‐up, 50%, 64%, 52%, and 37% of participants at levels 1–4, respectively, changed to a different PAM level (Spearman correlation = 0.47; p < 0.001). Home dialysis was associated with higher PAM scores when compared to in‐center hemodialysis in multivariable analyses, adjusted for sociodemographic variables, comorbidities, and predialysis nephrology care ( β = 5.74, 95% confidence intervals [CI]: 0.11–11.37 and 9.02, 95% CI: 3.03–15.02, at baseline and follow–up, respectively). Discussion: Although aggregated group scores and levels remained stable, intra‐individual patient activation changed significantly during the first 4 months of dialysis. This novel finding is foundational to future projects aiming to design interventions to improve patient activation.